Retention and delayed extinction of an instrumental response in the toad Rhinella arenarum: effects of overtraining - Puddington, Martin Miguel (2018)
Amphibians and mammals share common basic mechanisms for associative learning. However, it has been observed that some reinforcement paradigms produce opposite results. For example, increasing the number of reinforced trials during acquisition (overtraining) improves extinction in mammals, but it impairs extinction in amphibians. This study evaluates the effects of overtraining on response retention and subsequent delayed extinction after an 8-day retention interval in toads. Two groups of animals were trained in a runway for either 5 or 15 acquisition trials, one trial per day. Acquisition was followed by an 8-day retention interval without training, and then by 8 extinction trials. Nodifferences were observed in the rate of decay during the first trial of extinction or in the rate of delayed extinction. Since it had been previously observed that using the same parameters in the acquisition leads to a faster extinction in the 5-day group, the idea that mechanisms underlying extinction and spontaneous decay differ is considered.